Risk of myocardial infarction and stroke in bipolar disorder: a systematic review and exploratory meta‐analysis. (22nd May 2014) - Prieto, M. L.; Cuéllar‐Barboza, A. B.; Bobo, W. V.; Roger, V. L.; Bellivier, F.; Leboyer, M.; West, C. P.; Frye, M. A.
<x xml:space="preserve">Abstract</x> Objective To review the evidence on and estimate the risk of myocardial infarction and stroke in bipolar disorder. Method A systematic search using MEDLINE, EMBASE, PsycINFO, Web of Science, Scopus, Cochrane Database of Systematic Reviews, and bibliographies (1946 – May, 2013) was conducted. Case‐control and cohort studies of bipolar disorder patients age 15 or older with myocardial infarction or stroke as outcomes were included. Two independent reviewers extracted data and assessed quality. Estimates of effect were summarized using random‐effects meta‐analysis. Results Five cohort studies including 13 115 911 participants (27 092 bipolar) were included. Due to the use of registers, different statistical methods, and inconsistent adjustment for confounders, there was significant methodological heterogeneity among studies. The exploratory meta‐analysis yielded no evidence for a significant increase in the risk of myocardial infarction: [relative risk (RR): 1.09, 95% CI 0.96–1.24, P = 0.20; I2 = 6%]. While there was evidence of significant study heterogeneity, the risk of stroke in bipolar disorder was significantly increased (RR 1.74, 95% CI 1.29–2.35; P = 0.0003; I2 = 83%). Conclusion There may be a differential risk of myocardial infarction and stroke in patients with bipolar disorder. Confidence in these pooled estimates was limited by the small number of studies, significant heterogeneity and dissimilar methodological features.